Lucian Freud : portraits - Howgate, Sarah; Freud, Lucian; Auping, Michael; Richardson, John, 1924-; National Portrait Gallery (Great Britain); Modern Art Museum of Fort Worth (New Haven, CT : Yale University Press, 2012)
Surveys seven decades of the noted British artist's portraits; chronicles his life and artistic development; and offers interviews that discuss the challenge of making self-portraits and paintings, often nude, of family and friends.
Remembering Lucian Freud / John Richardson --Introduction / Sarah Howgate --People in rooms / Sarah Howgate --Freud from America / Michael Auping --Paintings and drawings --Etchings --Lucian Freud in conversation with Michael Auping --Chronology / Rosie Broadley.
"Published to accompany the exhibition Lucian Freud Portraits at the National Portrait Gallery, London, from 9 February to 28 May 2012 and the Modern Art Museum of Fort Worth, Texas, from 2 July to 28 October 2012"--P. [256]
Includes bibliographical references and index.
Keywords: Freud, Lucian -- Catalogs; Figurative painting, British -- Catalogs